2020
DOI: 10.3390/ijms21041461
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Expression as a Complementary Biomarker for Mismatch Repair Testing in Breast Cancer

Abstract: Mismatch repair (MMR) analysis in breast cancer may help to inform immunotherapy decisions but it lacks breast-specific guidelines. Unlike in other neoplasms, MMR protein loss shows intra-tumor heterogeneity and it is not mirrored by microsatellite instability in the breast. Additional biomarkers can improve MMR clinical testing. Phosphatase and tensin homolog (PTEN) inactivation is an early oncogenic event that is associated with MMR deficiency (dMMR) in several tumors. Here, we sought to characterize the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…In an elegant study, Djordjevic and collaborators observed that in non-endometrioid endometrial carcinomas, a PTEN-retained and/or wild-type status significantly co-occur with a retained positive expression of the MMR proteins [46]. Similarly, significant correlations between MMR proficiency, PTEN wild-type expression, and a better outcome have been recently reported in breast cancers [47]. These observations can be of clinical value not only for Lynch syndrome screening (e.g., endometrial cancer, colorectal cancer) but also for prognostication and immunotherapy prediction (e.g., breast cancer).…”
Section: Nuclear Pten and Modulation Of The Dna Damage Responsementioning
confidence: 89%
See 2 more Smart Citations
“…In an elegant study, Djordjevic and collaborators observed that in non-endometrioid endometrial carcinomas, a PTEN-retained and/or wild-type status significantly co-occur with a retained positive expression of the MMR proteins [46]. Similarly, significant correlations between MMR proficiency, PTEN wild-type expression, and a better outcome have been recently reported in breast cancers [47]. These observations can be of clinical value not only for Lynch syndrome screening (e.g., endometrial cancer, colorectal cancer) but also for prognostication and immunotherapy prediction (e.g., breast cancer).…”
Section: Nuclear Pten and Modulation Of The Dna Damage Responsementioning
confidence: 89%
“…Genomic scars in the MMR system are relatively rare in breast cancer, being reported in~2% of cases [49]. However, this subject is controversial in literature given the lack of companion diagnostics and/or tumor-specific guidelines for MMR analysis [47,[49][50][51][52][53][54]. Unlike in endometrial and colorectal cancers, MSI is restricted to a minority of breast cancers showing MMR protein loss [54].…”
Section: Nuclear Pten and Modulation Of The Dna Damage Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The tumor suppressor PTEN has an important role as a lipid and protein phosphatase, regulating cell proliferation, adhesion, and invasion, and DNA damage repair [ 67 ]. PTEN dephosphorylates the PIP3 to create PIP2, and thereby inhibits the PI3K/AKT pathway [ 68 , 69 ]. The PI3K/AKT pathway is dysregulated in GBM and supports cell proliferation by promoting the presence of anti-apoptotic signals in the cell [ 70 ].…”
Section: Molecular Pathogenesis Of Gbmmentioning
confidence: 99%
“…However, many Centers have recently adopted panels consisting of mononucleotide markers due to their higher sensitivity and specificity compared to dinucleotide markers [47]. Unlike in other types of tumors (e.g., breast cancer), there is a general agreement on the high correlation between MSI testing and MMR immunohistochemistry in GEC [48][49][50][51][52][53]. Epigenetic silencing of MLH1 by promoter hypermethylation is a crucial event that leads to dMMR both in the sporadic setting (more than 50% of MSI GCs) and in familial MSI GEC cases [43,54].…”
Section: Mmr Clinical Testing In Gec: Rationale Currently Available mentioning
confidence: 99%